CRISPR-Cas9 Potential in Eradicating HIV Latent Reservoir as The Up-to-date Therapy For HIV-1 - Jessica Putri Salim; Friska Anggraini; Safa Nabila Putri; Ziske Maritska (Sriwijaya Journal of Medicine, 2021)
According to the Ministry of Health in Indonesia, in 2018, there are about 640 thousand cases of people with HIV within the death rate of 38 thousand people. This number grows annually, in fact, according to WHO, there are approximately 38 million people who are diagnosed with HIV in the world in 2019. Thus, HIV-AIDS is a dangerous health problem and needs to be taken care of as soon as possible. HIV (Human Immunodeficiency Virus) is a retrovirus that got its name from the infecting immune cells in the human body. There are two types of HIV, named HIV-1 and HIV-2. Both have the same basic gene arrangement, transmission process, intracellular replication lane, and both cause AIDS. The differences between them are the HIV-1 spreads globally, while HIV-2 locally happens in West Africa. Currently, ART (Antiretroviral Therapy) is the most commonly used method of treatment for HIV-1. Treatment for HIV-1 with ART is effective in controlling HIV-1 virus replication but has not been able to completely eradicate the latent viral reservoir. In the past few years, it is known that there is a CRISPR (Clustered Regularly Interspaced Short Palindromic Repeat) method that can modify genes (DNA) in the body of an organism. However,apart from its potential in handling HIV-1, there are still obstacles in the mechanism.